2012
DOI: 10.1902/jop.2011.110261
|View full text |Cite
|
Sign up to set email alerts
|

Destructive Membranous Periodontal Disease (Ligneous Gingivitis): A Literature Review

Abstract: Ligneous gingivitis is a rare periodontal disorder closely associated with ligneous conjunctivitis and plasminogen deficiency. Its diagnosis may be supported by the finding of genetic mutations responsible for the condition. Research is focusing on the future development of an effective therapy capable of arresting the destructive evolution of the disease. Additional studies, investigating features such as probing depth and attachment loss, are needed for the appropriate classification of this periodontal dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 58 publications
1
33
1
Order By: Relevance
“…All inherited forms of HIES express elevated IgE. Distinguishing features associated with AD-HIES are connective tissue and skeletal abnormalities to include maxillofacial irregularities and a prominent arched palate, recurrent skin and pulmonary infections (eczema, pneumatoceles), recurrent fungal infections, prolonged healing of infections, retained and/ or delayed shedding of primary teeth, and ligneous gingivitis/periodontitis (destructive membranous periodontal disease) (Hatori et al, 1993;Gunhan et al, 1994Gunhan et al, , 1999Grimbacher et al, 1999;Aldous et al, 2007;Freeman et al, 2009;Deepa et al, 2012;Sivolella et al, 2012). Grimbacher et al revealed that over 70% of their studied patient population with HIES had retained primary dentition (Grimbacher et al, 1999).…”
Section: Oral Diseasesmentioning
confidence: 99%
“…All inherited forms of HIES express elevated IgE. Distinguishing features associated with AD-HIES are connective tissue and skeletal abnormalities to include maxillofacial irregularities and a prominent arched palate, recurrent skin and pulmonary infections (eczema, pneumatoceles), recurrent fungal infections, prolonged healing of infections, retained and/ or delayed shedding of primary teeth, and ligneous gingivitis/periodontitis (destructive membranous periodontal disease) (Hatori et al, 1993;Gunhan et al, 1994Gunhan et al, , 1999Grimbacher et al, 1999;Aldous et al, 2007;Freeman et al, 2009;Deepa et al, 2012;Sivolella et al, 2012). Grimbacher et al revealed that over 70% of their studied patient population with HIES had retained primary dentition (Grimbacher et al, 1999).…”
Section: Oral Diseasesmentioning
confidence: 99%
“…9 Almost three-quarters of the case reports related to ligneous gingivitis are in the Turkish population. 6,10 Consanguinity rates are very high in our country and this may be responsible for this relatively higher incidence of ligneous gingivitis in this population. Parents of our patient are cousins, consistently with literature.…”
Section: Discussionmentioning
confidence: 93%
“…Because fibrin degradation is limited, the woundhealing process is disrupted at the stage of granulation tissue formation (Mehta & Shapiro, 2008;Pantanowitz et al, 2004;Sivolella, De Biagi, Sartori, Berengo, & Bressan, 2012).…”
Section: Introductionmentioning
confidence: 99%